234k views
1 vote
I NEED HELP! If f(x)= 5x^2-3 and g(x)=x^2-4x-8, find (f-g)(x).

User Gustavo
by
4.9k points

1 Answer

4 votes

Answer:

(f - g)(x) = 4x² + 4x + 5

General Formulas and Concepts:

Pre-Algebra

  • Distributive Property

Algebra I

  • Combining Like Terms

Explanation:

Step 1: Define

f(x) = 5x² - 3

g(x) = x² - 4x - 8

(f - g)(x) is f(x) - g(x)

Step 2: Find (f - g)(x)

  1. Substitute: (f - g)(x) = 5x² - 3 - (x² - 4x - 8)
  2. Distribute -1: (f - g)(x) = 5x² - 3 - x² + 4x + 8
  3. Combine like terms: (f - g)(x) = 4x² + 4x + 5
User Nayeem Zen
by
5.2k points